Unpacking drivers of Micro-Social Entrepreneurs in a less affluent economy: The cases of Type II social business - Ahmed, T.; Islam, T.; Sultan, P.; Marimuthu, M. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This paper concerns the social changes intended by social entrepreneurs when tied to social business models. Practical business model innovation can fulfil high and low social needs at both micro and macro levels. Our multi-method empirical work unpacks how this type of business model copes with challenges in challenging economic, social and political conditions. Our analysis traces general inquiries on social entrepreneurs operating a Type II social business model and the process model associated with their success. Using data from Bangladeshi micro social enterprises, we apply social businesses models and propose an extended theoretical framework for Type II social business.
Keywords: Social business, antecedents to value, business models, Type II business mode, Bangladesh